Effect of Brief Pharmacist Counseling on Knowledge, Perception, Adherence, and Hemoglobin in Second-Trimester Pregnancy at a Community Health Center - Sri Suprapti; Endang Darmawan; Eliza Dwinta; Win Win Khaing Shwe; Emelda Emelda; Fadilatul Layalli; Ratih Devi Alfiana (Alma Ata University Press, 2026)
Background: Anemia in pregnancy increases the risk of maternal mortality and fetal damage. The primary cause is iron deficiency. In 2018, 73.2% of pregnant women in Indonesia received iron supplements, yet anemia remained common, affecting 48.9% of them. Objective: This study aims to investigate the influence of Brief Counseling 5A on knowledge, perception, compliance, and Hb levels in second-trimester pregnant women taking Iron (III) Hydroxide Polymaltose Complex (IPC) tablets at the X’s Public Health Center in Yogyakarta. Methods: This quasi-experimental study used a pre-test and post-test design without a control group and was conducted from November 2018 to April 2019 with 39 pregnant women. Measurements of knowledge, perception, and compliance were taken at the pre-test (1st day) and post-test (31st day) for those who received Brief Counseling 5A. Results: Brief Counseling 5A significantly increased mean pre-test and post-test scores for knowledge, perception, and compliance, with a significance value of 0.001 (p<0.050). The mean pre-test knowledge score was 64.36 ± 2.69. The post-test score was 90.26 ± 1.60. The mean pre-test perception score was 28.26 ± 0.56, and the post-test perception score was 33.31 ± 0.60. The mean pre-test compliance level score was 56.15 ± 3.28, and the post-test was 86.41 ± 2.06. Each parameter had a p-value < 0.05. Meanwhile, the mean pre-test Hb value was 11.98 ± 0.23 g/dL, while the mean post- test Hb value was 11.67 ± 0.21 g/dL, with a p-value of 0.117. Conclusion: Brief Counseling 5A can significantly increase knowledge, perception, and compliance. However, there was no increase in Hb levels among second-trimester pregnant women who consumed IPC tablets at the Public Health Center of Banguntapan III, Bantul.